2005
DOI: 10.1063/1.1870131
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of B deactivation control by F co-implantation

Abstract: Fluorine-enhanced boron diffusion in germanium-preamorphized silicon J. Appl. Phys. 98, 073521 (2005); 10.1063/1.2084336 Activation improvement of ion implanted boron in silicon through fluorine co-implantation J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 11 publications
(18 reference statements)
2
43
0
Order By: Relevance
“…The vacancies trapped by the F atoms are in turn able to trap the interstitials migrating from the EOR region and thus significantly reduce B diffusion, as observed by Cowern et al 1 VEPAS and SIMS results indicate that the concentration of the complexes, to within 25%, decreased from ͓͑4.5/ n͒ to ͑2.6/ n͔͒ ϫ 10 19 cm −3 between 15 and 120 s annealing times at 800°C, but dropped significantly to ͑4.3/ n͒ ϫ 10 18 cm −3 after annealing for 2700 s.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…The vacancies trapped by the F atoms are in turn able to trap the interstitials migrating from the EOR region and thus significantly reduce B diffusion, as observed by Cowern et al 1 VEPAS and SIMS results indicate that the concentration of the complexes, to within 25%, decreased from ͓͑4.5/ n͒ to ͑2.6/ n͔͒ ϫ 10 19 cm −3 between 15 and 120 s annealing times at 800°C, but dropped significantly to ͑4.3/ n͒ ϫ 10 18 cm −3 after annealing for 2700 s.…”
mentioning
confidence: 51%
“…The application of particular interest here concerns ultrashallow B implantation into preamorphized Si regrown via solid-phase epitaxy ͑SPE͒; efficient activation of the B while limiting its diffusion is the key to the formation of ultrashallow junctions. Recent work by Cowern et al 1 showed that F in B-implanted Si can form clusters that trap interstitals ͑I͒ released from the band of end-of-range ͑EOR͒ defects, which in turn both retard the transient enhanced diffusion of B implants and significantly decrease their deactivation. Kham et al 2 linked F found at half the projected ion range to the formation of clusters of F with vacancies ͑V͒ in this region.…”
mentioning
confidence: 99%
“…23 In germanium, the EOR defects are relatively short lived and do not necessarily follow a classical Ostwald ripening process. 27 However, due to the greater likelihood of P n V m cluster formation, rather than P n I m formation, the thermal stability of the activated profile largely depends on the vacancy population, which often relies on thermal generation and injection from surfaces.…”
mentioning
confidence: 99%
“…14,15 SPER has recently been explored for p-type [16][17][18] and n-type 19,20 dopant activation in germanium but a number of key issues remain. Deactivation kinetics have been studied in silicon [21][22][23] but this aspect is largely unexplored at this point of time for n-type dopants in germanium. Moreover, optimization of process variables such as implants and recrystallization temperatures require fine tuning.…”
mentioning
confidence: 99%
“…[5][6][7] Kalyanaraman et al 8,9 used Au labeling to study the formation of nanovoids in Si. The aim of the current research is to investigate the evolution of vacancy-type defects in Si with annealing temperature, from divacancies in asimplanted samples through small clusters of n vacancies V n (n ¼ 3-6) to nanovoids, using the technique of variableenergy positron annihilation spectroscopy (VEPAS).…”
mentioning
confidence: 99%